Identification of SEC62 as a potential marker for 3q amplification and cellular migration in dysplastic cervical lesions. Issue 1 (December 2016) - Linxweiler, Maximilian; Bochen, Florian; Schick, Bernhard; Wemmert, Silke; Al Kadah, Basel; Greiner, Markus; Hasenfus, Andrea; Bohle, Rainer-Maria; Juhasz-Böss, Ingolf; Solomayer, Erich-Franz; Takacs, Zoltan
Abstract Background Chromosome 3 amplification affecting the 3q26 region is a common genomic alteration in cervical cancer, typically marking the transition of precancerous intraepithelial lesions to an invasive phenotype. Though potential 3q encoded target genes of this amplification have been identified, a functional correlation of potential oncogenic function is still missing. In this study, we investigated copy number changes and the expression level ofSEC62 encoded at 3q26.2 as a new potential 3q oncogene in dysplastic cervical lesions and analyzed its role in cervical cancer cell biology. Methods Expression levels of Sec62 and vimentin were analyzed in liquid based cytology specimens from 107 women with varying grades of cervical dysplasia ranging from normal cases to cancer by immunofluorescence cytology. Additionally, a subset of 20 representative cases was used for FISH analyses targetingSEC62 . To further explore the functional role of Sec62 in cervical cancer, HeLa cells were transfected with aSEC62 plasmid orSEC62 siRNA and analyzed for their proliferation and migration potential using real-time monitoring and trans-well systems as well as changes in the expression of EMT markers. Results FISH analyses of the swabbed cells showed a rising number ofSEC62 gains and amplifications correlating to the grade of dysplasia with the highest incidence in high grade squamous intraepithelial lesions and squamous cell carcinomas. When analyzing the expression level of Sec62 and vimentin, we found a gradually increasing expression level of both proteins according to the severity of the dysplasia. In functional analyses, SEC62 silencing inhibited andSEC62 overexpression stimulated the migration of HeLa cells with only marginal effects on cell proliferation, the expression level of EMT markers and the cytoskeleton structure. Conclusions Our study suggestsSEC62 as a target gene of 3q26 amplification and a stimulator of cellular migration in dysplastic cervical lesions. Hence, SEC62 could serve as a potential marker for 3q amplification, providing useful information about the dignity and biology of dysplastic cervical lesions.